Effectiveness of Surgical Interventions in Chronic Venous Insufficiency: An Evidence-Based Systematic Review - Tama, I Putu Rangga Rasnadea; Prayogo, Danniel Loogman; Manikasari, Putu Indri; Sudiartha, I Putu Gede; Pretangga, Anak Agung Ngurah (Riviera Publishing, 2024)
Chronic Venous Insufficiency (CVI) is a disease that can significantly affect patients' quality of life. Although modern surgical therapies such as endovenous thermal ablation (ETA), iliac vein stenting, and others have been introduced, the effectiveness and safety of each procedure needs to be further evaluated. This study aims to evaluate the effectiveness and safety of modern surgical interventions in the management of CVI, focusing on clinical outcomes such as ulcer healing, pain reduction, and improvement in patient quality of life. This systematic review was conducted following PRISMA guidelines by screening literature from PubMed, ScienceDirect, Google Scholar, and Cochrane Library between 2014 and 2024. Of the 17,500 articles identified, 10 studies were included through a rigorous selection process. Analysis was performed based on study design, population, intervention type, clinical outcomes, and safety profile. Endovenous thermal ablation showed an anatomical success rate of more than 96% with long-term clinical benefits. Iliac vein stenting significantly improved symptoms of deep vein obstruction (VAS: 9 to 2.5) with a primary patency rate of 92%. Methods such as mechanochemical ablation (MOCA) and cyanoacrylate embolization (CAE) offer minimally invasive approaches with low complication rates and fast recovery times. The combination of early ablation and compression therapy accelerates healing of chronic venous ulcers (median healing time: 56 vs. 82 days). Modern surgical interventions are proven effective and safe in the management of CVI, with thermal ablation as the gold standard and iliac vein stenting as the superior option for deep vein obstruction. This evidence-based approach provides important guidance for personalizing CVI therapy in the future. Further research is needed to evaluate long-term sustainability and to optimize evidence-based clinical guidelines.